" HAWKEYE" for gymnastics? Automatic evaluation of hold time in still rings exercises during the european championships gymnastics 2014 - Aarts, M.; Pluk, A. (Conference: Science and Engineering Conference on Sports Innovation 2016, 2016)
During the European Championships 2016 in Bern, 278 complete datasets of ring exercises were recorded, of which 214 datasets of the qualifications (CI). Within these 214 qualification exercises, 1146 hold elements were executed. On average, in 15.1% of these hold elements a hold error was reported by the Smart Rings Jury Tool (which means the button was pressed for less than 2.0 seconds), while in 14.5% of the hold elements indeed a deduction was given after evaluation of the judges. This shows the benefit of the combined force and video signals. The statistics show that in Senior competition a larger number of hold elements are performed per exercise, but also a higher percentage of hold errors were found by the Smart Rings Jury Tool (9.7% and 20.7% respectively) and consequently also a higher percentage of deductions were given after evaluation (10.7% and 18.6% respectively). This indicates that implementation of the tool during Senior competition is even more important for accurate and objective evaluation of strength and hold elements. In Junior CI on average 18.4% (7.1%-32.1%) of the total deduction consisted of HT deductions, proving that it is a very important aspect of still rings judging.